An Analysis of Stress Among the Women Mill Workers in Dindigul District of Tamil Nadu - Poorna, D. B.; Anandaraj, P. (Prabandhan: Indian Journal of Management, 2013)
Women’s employment is an index of a society’s modernization. It helps them to initiate and motivate the process of change towards social justice and build up human resources. The traditional role of a man has been to earn money for the running of the home. This has changed to a great extent. Now, working women contribute to the expenses of running their homes as well. The working women have added responsibilities of looking after both - the family and the workplace. Hence, due to a lot of mental pressure, women develop both physical and psychological problems. Because of their busy schedule both at home and at the workplace, women are short of time to perform all their duties. In spinning mills, most of the workers are women employees. The Dindigul District is the one of the largest industrial districts in Tamil Nadu. It is home to a major textile spinning industry, which has the highest capacity within Tamil Nadu. The work environment of the mills causes a lot of stress to the women because of continuous long working hours, ill-health, physical and mental sickness, which leads to fatigue, stress, auditory damage, breathing problems, and so on. Hence, the present study aimed to understand the factors that caused stress to the mill workers and also provides some suggestions which can be used by the mill workers to overcome stress.